2006
DOI: 10.1007/s00572-006-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi enhance fruit growth and quality of chile ancho (Capsicum annuum L. cv San Luis) plants exposed to drought

Abstract: The effect of arbuscular mycorrhizal fungi (AMF) and drought on fruit quality was evaluated in chile ancho (Capsicum annuum L. cv San Luis). AMF treatments were (1) Glomus fasciculatum (AMFG), (2) a fungal species consortium from the forest "Los Tuxtla" in Mexico (AMFT), (3) a fungal species consortium from the Sonorian desert in Mexico (AMFD), and (4) a noninoculated control (NAMF). Plants were exposed to a 26-day drought cycle. Fruit quality was determined by measuring size (length, width, and pedicel length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 23 publications
2
40
1
13
Order By: Relevance
“…This is in contrast to many other studies documenting a positive impact of root inoculation with beneficial rhizosphere microorganisms on fruit quality parameters (Charron et al, 2001;Kaya et al, 2003;Mena-Violante et al, 2006). An increase in antioxidant activity and a higher lycopene and shoot and fruit potassium content were also reported for tomato fruits from AMFinoculated plants (Ordookhani et al, 2010).…”
Section: Discussioncontrasting
confidence: 52%
“…This is in contrast to many other studies documenting a positive impact of root inoculation with beneficial rhizosphere microorganisms on fruit quality parameters (Charron et al, 2001;Kaya et al, 2003;Mena-Violante et al, 2006). An increase in antioxidant activity and a higher lycopene and shoot and fruit potassium content were also reported for tomato fruits from AMFinoculated plants (Ordookhani et al, 2010).…”
Section: Discussioncontrasting
confidence: 52%
“…For example, AM fungi improved growth and fruit quality in Capsicum annuum L. cv. 'San Luis' grown under water deficit (Mena-Violante et al 2006). Similarly, mycorrhizae improved growth in perennial trees such as Fagus sylvatica (Shi et al 2002) and Pinus radiata (Ortega et al 2004) by improving water relations.…”
Section: Introductionmentioning
confidence: 98%
“…TEC seed treatments that had a dry weight of higher than 0.66 g plant were 14, 1 and 11; TRA in the inoculum treatments 1, 13 and 14 had a higher weight to 0.68 g. Mena-Violante et al (2006), found no effect by inoculation with AMF on the dry weight of plant root width pepper (Capsicum annuum L.); however, Ortas et al (2011), reported that, the inoculation with different AMF increased the PSR and shoot dry weight. PSR increased, shoot and total dry weight is also reported by Sensoy et al (2007) using two strains of AMF in eight genotypes of chili peppers.…”
Section: Peso Seco De Hoja Tallo Raíz Y Peso Seco Totalmentioning
confidence: 97%
“…Los tratamientos del inóculo TEC que tuvieron un peso seco de planta superior a 0.66 g fueron 14, 1 y 11; en el inóculo TRA los tratamientos 1, 13 y 14 tuvieron un peso mayor a 0.68 g. Mena-Violante et al (2006) no encontraron efecto por la inoculación con HMA en el peso seco de raíz de plantas de chile ancho (Capsicum annuum L.), pero Ortas et al (2011) reportan que la inoculación con diferentes HMA incrementaron el PSR así como el peso seco de brotes. El aumento de PSR, de brotes, así como del peso seco total es reportada también por Sensoy et al (2007) al utilizar dos cepas de HMA en ocho genotipos de chiles.…”
Section: Peso Seco De Hoja Tallo Raíz Y Peso Seco Totalunclassified